Primary Effusion Lymphoma: Small Bowel Recurrence After Stem Cell Transplant. Issue 11 (19th November 2021) - Mushtaq, Sarah; Prabakaran, Sabrina; Elharake, Maher; Mirza, Sayeef; Ravindran, Adharsh; Faramand, Rawan; Sokol, Lubomir
ABSTRACT: Primary effusion lymphoma (PEL) is a rare AIDS-associated non-Hodgkin lymphoma, growing in the serous body cavities as a lymphomatous effusion. The endoscopic features of PEL can mimic Kaposi sarcoma (KS). We present a case where PEL presented as small intestinal masses which had a similar macroscopic appearance to KS. Endoscopic evaluation was used with biopsies which confirmed the diagnosis of PEL. PEL is a differential of gastrointestinal KS. Accurate diagnosis is crucial for prognostication in these patients. Our case emphasizes that PEL presenting as intestinal tumors can mimic KS macroscopically. Although treatment for PEL and KS includes standard chemotherapy with concurrent antiretroviral therapy, early detection of PEL can improve overall survival in these patients.